تحقيق المخطوطات في الدراسات الإسلامية ومقصد الإنتاجية الاستثمارية - عيساوي, عبد الغاني (جامعة الوادي - University of Eloued, 2022)
الملخص: تهدف الورقة البحثية إلى تحليل ومناقشة بيان لجنة بغداد سنة 1980م، باعتبارها أول محاولة رسمية لتبني قواعد تحقيق المخطوطات ونشر النصوص، والتي دعت إلى تخصيص كرسي خاص بتعليم قواعد تحقيق المخطوطات في الجامعات العربية، مع جعل هذا العلم من متطلبات الحصول على شهادة الدراسات العليا الماجستير أو الدكتوراه، كما تهدف الورقة إلى بيان أن عملية تحقيق المخطوط لا تنتهي بمجرد إكماله ورصفه في المكتبات إخراجا وتحقيقا، بل أنها تبدأ من تلك المرحلة، بما أطلقتُ عليه بالقراءة الإنتاجية الاستثمارية، التي نولِّد من خلالها منتوجا علميا موازيا لما في المخطوط مواكبا لمتطلبات العصر، معينا على فهم قضايانا ومشكلاتنا، في ربط وثيق للماضي بالحاضر، كل ذلك باستشهادات من تراثنا العلمي الجزائري، وبمنهجية استقرائية تحليلية. Summary: The research aims to analyze and discuss the statement of the Baghdad Committee in 1980, as it is the first official attempt to adopt the rules of manuscript realization and publication of texts, which called for allocating a special chair for teaching the rules of manuscript realization in the Arab universities, while making this science one of the requirements for obtaining a master’s or postgraduate degree . It aims also on showing that the process of achieving the manuscript does not end with just completing and paving it in the libraries for output and realization , but rather ,it starts from that stage, with what it called investment productive reading, through which we generate a scientific product parallel to what is in the manuscript that keeps pace with the requirements of the times, specific on understanding our issues and problems, in a close link between the past and the present, all with citations from our Algerian scientific heritage, and with an inductive and analytical methodology.
The realization of the manuscripts in the Islamic studies, and the goal of the investment productivity
مقال
Keywords: المخطوطات، الدراسات الإسلامية، الإنتاجية، الاستثمارية، تحقيق; manuscripts; Islamic studies; growth; investment